Evaluasi Hukum Pemerintahan Daerah Terhadap Implementasi Pajak Karbon Sebagai Instrumen Green Fiscal Policy: Legal Evaluation of Local Government on the Implementation of Carbon Tax as an Instrument of Green Fiscal Policy - Ibrahim, Vicky; S. Hasan, Yeti; Sholehah, Nur Lazimatul Hilma (Constitution Journal, 2025)
Carbon tax is a fiscal instrument designed to control carbon emissions while supporting sustainable development. However, its implementation at the regional level still faces problems of authority and institutional readiness that are not yet optimally integrated. This study aims to evaluate the legal framework, the authority of local governments, and institutional preparedness in the implementation of carbon tax as an instrument of green fiscal policy, with a specific focus on Gorontalo Province. The research method employed is normative legal research with a statutory approach, complemented by empirical data obtained through interviews with relevant agencies, namely the Regional Development Planning Agency (Bappeda), the Regional Revenue Agency (Bapenda), and the Environmental Agency (DLH). The findings indicate that the regulation of carbon tax under Law Number 7 of 2021 on the Harmonization of Tax Regulations remains centralized and does not provide attribution of authority to local governments. Institutional preparedness at the regional level is also limited, as no regulation or coordination mechanism integrates the functions of planning, collection, and supervision. In addition, the main challenges identified include the absence of regional regulations, potential socio-economic burdens, and the lack of a transparent fiscal governance mechanism. This study concludes that the success of carbon tax implementation as a green fiscal instrument requires strengthening of the legal framework, institutional capacity, and fiscal governance at the regional level. Abstrak Pajak karbon merupakan instrumen fiskal yang dirancang untuk mengendalikan emisi karbon sekaligus mendukung pembangunan berkelanjutan. Namun, pelaksanaannya di tingkat daerah masih menghadapi persoalan kewenangan dan kelembagaan yang belum terintegrasi secara optimal. Penelitian ini bertujuan mengevaluasi kerangka hukum, kewenangan pemerintah daerah, serta kesiapan kelembagaan dalam implementasi pajak karbon sebagai instrumen green fiscal policy, dengan fokus kajian di Provinsi Gorontalo. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan peraturan perundang-undangan, dilengkapi dengan data empiris melalui wawancara dengan instansi terkait, yaitu Bappeda, Bapenda, dan Dinas Lingkungan Hidup. Hasil penelitian menunjukkan bahwa pengaturan pajak karbon dalam Undang-Undang Nomor 7 Tahun 2021 tentang Harmonisasi Peraturan Perpajakan masih bersifat sentralistik dan tidak memberikan atribusi kewenangan kepada pemerintah daerah. Kesiapan kelembagaan di daerah juga terbatas karena belum ada regulasi maupun mekanisme koordinasi yang mengintegrasikan fungsi perencanaan, pemungutan, dan pengawasan. Selain itu, tantangan utama yang dihadapi mencakup keterbatasan regulasi daerah, potensi dampak sosial-ekonomi, serta belum adanya tata kelola fiskal yang transparan. Penelitian ini menyimpulkan bahwa keberhasilan implementasi pajak karbon sebagai instrumen fiskal hijau memerlukan penguatan aspek hukum, kelembagaan, dan tata kelola pada tingkat daerah.